Effect of organizational factors on lending levels by Digital Credit Providers in Kenya - Kemboi, R. J. (Strathmore University, 2025)
Organizational factors are vital in an organization when it comes to the decision-making process. Digital credit providers deploy various strategies to maintain optimal credit levels and realize effective credit management. Such measures significantly impact the loan provision and dictate the financial condition of the lender. The increased utilization of digital credit, among consumers with low financial literacy amid high non-performing loans, have heightened financial instability risks of the lenders. The purpose of this study was to establish the effect of organizational factors on lending levels by Digital Credit Providers (DCPs). The study was based on two theories namely the information asymmetry theory and the resource-based view theory. The specific objectives were; to determine the effect of firm size on lending levels by DCPs in Kenya, to determine the effect of age on lending levels by DCPs in Kenya, to determine the effect of corporate governance on lending levels by DCPs, to determine the effect of credit risk on lending levels by DCPs and to determine the moderating effect of regulatory factors on the relationship between organizational factors and lending levels of DCPs. The study employed the descriptive-cross sectional research design. The study’s population was the 85 DCPs licensed by the Central Bank of Kenya (CBK) as at 1st, March 2025. The study was a census of all the 85 licensed digital credit providers in Kenya. The study used primary data to be collected with the aid of a structured questionnaire. Data was collected from owners, managers and directors of DCPs. The correlation analysis for the variables namely age, size, corporate governance and credit risk management revealed a positive correlation between predicting variables and the outcome variable. The findings revealed that the a statistically significant relationship between organizational factors and lending levels of DCPs. The considered organizational factors namely firm size, age, corporate governance and credit risk management contribute substantially to lending levels by DCPs. The moderating effect of regulatory factors on the relationship between organizational factors and lending levels was also statistically significant. The recommendations of the study include; Digital credit providers should expand their asset base, broaden market reach, and diversify loan products through strategic partnerships and improved digital infrastructure. Newer firms must adopt established best practices to build credibility and secure long-term financing. Strengthening corporate governance by ensuring board diversity, gender inclusivity and continuous capacity building will enhance sound decision making. Finally, credit risk management with advanced analytics is essential for responsible lending and long-term stability. Various limitations were encountered in the study which include reliance on self-reported data from DCPs, which may be biased, the utilization of the cross-sectional design was limiting in terms of establishment of causal relationships, finally, the findings may not be generalized for other regulatory and economic contexts. The findings will contribute to knowledge on credit lending by DCPs which may invoke policies and good practices by digital lenders hence strengthening the performance of the sector.
Full - text thesis